UV-PROTECTIVE PROPERTIES OF EXTRACTS OBTAINED FROM TRANSFORMED AND NON-TRANSFORMED ROOTS OF ARTEMISIA GENUS PLANTS - ЧОПЕЙ, Мар'яна; ДУПЛІЙ, Володимир; МАТВЄЄВА, Надія; АФАНАСЬЄВА, Катерина (ВПЦ "Київський університет" - Publishing center "Kyiv University", 2025)
Background. Medicinal plant extracts are widely used in traditional and non-conventional medicine. Special interest is given to extracts obtained from transgenic so-called "hairy" roots. Usually, such roots are characterized by a high content of biologically active components. However, such plant transformation can lead to the appearance of both undesirable effects of the obtained extracts (e.g., a genotoxic effect) and positive effects (e.g., antioxidant and UV-protective properties). In this work the content of flavonoids in extracts of roots of three species of the Artemisia genus, as well as their potential genotoxic and UV-protective properties, were studied. Methods. Transgenic roots of Artemisia annua, A. vulgaris and A. tilesii with the inserted roll gene were obtained using Agrobacterium rhizogenes A4 mediated transformation. Water extracts were prepared according to a standard procedure. Total flavonoid amount was estimated spectrophotometrically. Comet assay was used as an approach to evaluate extracts genotoxicity and UV-protective properties. Results. It was shown that the content of flavonoids in extracts obtained from the transgenic plants is more than 2 times higher than that for control plants. Extracts obtained from A. vulgaris and A. annua had no genotoxic effect, while extracts obtained from A. tilesii had a weak but statistically significant mutagenic effect. A. vulgaris extracts had pronounced UV-protective properties, which were correlated with the content of flavonoids in these extracts. Conclusions. Extracts of plants studied mostly did not show a genotoxic effect, but had UV-protective properties. The ability of extracts to reduce the negative effects of UV-irradiation depends on the concentration of flavonoids: the increased content of these compounds in transgenic plants led to almost 3-fold decrease in the relative amount of DNA in the comet tails.

Вступ. Екстракти лікарських рослин широко використовуються у традиційній та нетрадиційній медицині. Особливий інтерес приділяється екстрактам, отриманим із трансгенних, так званих “бородатих”, коренів. Зазвичай такі корені характеризуються підвищеним вмістом біологічно активних компонентів. Проте така трансформація рослин може призводити до появи як небажаних ефектів отриманих екстрактів (наприклад, їх генотоксичний ефект), так і мати позитивний ефект (наприклад, антиоксидантні та УФ-протекторні властивості). У цій роботі було досліджено вміст флавоноїдів у екстрактах “бородатих” коренів трьох видів трансформованих і нетрансформованих рослин роду Artemisia, а також їх потенційні генотоксичні та УФ-протекторні властивості. Методи. Трансгенні корені Artemisia annua, A. vulgaris і A. tilesii з вбудованим геном roll були отримані за допомогою Agrobacterium rhizogenes A4-опосередкованої трансформації. Водні екстракти готували за стандартною методикою. Загальну кількість флавоноїдів оцінювали спектрофотометрично. Кометний електрофорез використовувався як підхід для оцінки генотоксичності екстрактів і їх УФ-протекторних властивостей. Результати. Показано, що вміст флавоноїдів в екстрактах, отриманих із трансгенних рослин, більш ніж у 2 рази перевищує їх вміст у контрольних рослин. Екстракти, отримані з A. vulgaris і A. annua, не мали генотоксичної дії, у той час як екстракти, отримані з A. tilesii, мали слабку, але статистично значущу мутагенну дію. Екстракти A. vulgaris мали виражені УФ-протекторні властивості, які були скорельовані з вмістом флавоноїдів у цих екстрактах. Висновки. Екстракти дослідних рослин здебільшого не виявляли генотоксичної дії, але мали УФ-протекторні властивості. Здатність екстрактів знижувати негативний вплив УФ-опромінення залежить від концентрації флавоноїдів: підвищення вмісту цих сполук у трансгенних рослинах призвело до зменшення відносної частки ДНК у хвостах комет майже в 3 рази.
УФ-ПРОТЕКТОРНІ ВЛАСТИВОСТІ ЕКСТРАКТІВ, ОТРИМАНИХ ІЗ ТРАНСФОРМОВАНИХ І НЕТРАНСФОРМОВАНИХ КОРЕНІВ РОСЛИН РОДУ ARTEMISIA
Keywords: "hairy" root extracts; Artemisia spp.; flavonoids; UV-protective properties; genotoxicity; comet assay; "hairy" root extracts; Artemisia spp.; flavonoids; UV-protective properties; genotoxicity; comet assay; екстракти "бородатих" коренів; види Artemisia spp.; флавоноїди; УФ-протекторні властивості; генотоксичність; кометний електрофорез